Origami - Johnson-Flint, Gillian (Edison, N.J. Chartwell Books, 1996)
Thirty creative paper projects to make for family and friends.
"A Quintet book."
Subtitle on jacket: 30 awesome projects for the creative kid.
Keywords: Origami